Knowledge-Based Emergency Planning for Storage Tank Farms - Vaclav Nevrly; Petr Bitala; Petra Nevrla; Michal Strizik (Communications - Scientific letters of the University of Zilina, 2008)
Major accidents in storage tank farms can result in severe threats for emergency responders, neighbouring population and the environment as it was observed in the case of Buncefield (2005). The numerical modelling of dangerous phenomena is an important tool to support emergency planning for such complicated events. For this purpose, the case study in crude oil tank farm involving selection of reference accident scenario, CFD simulation of tank fire and prediction of delay to boilover was performed. The results were used to review the existing emergency plans and to enhance the tactical preparedness of emergency responders.